Studies on Shrinkage Behaviour of Robinia pseudacacia Timber - Singh, H. P.; Pandey, C. N.; Sharma, S. N. (Indian Forester, 1990)
Shrinkage behaviour of Robina pseudacacia was studied and its total tangential, radial and volumetric shrinkage was found as 7.7 %, 5.1 % and 10 % respectively which compares well with timbers like, Adina cordifolia, Dillellia pentagyna, Holoptelea integrifolia and Machiluus macrantha. Its retention of shape and size relative to teak was found as 73 % compared to teak taken as 100. The mean Inter-section Point (I.S.P) was estimated and found as 24 %. The species may be classed as moderately stable in shape and size, comparable to species commonly in use for furniture and joinery.